Satisfaction of lower limb amputees with their prostheses and with the clinical services- a cross-sectional survey - Bari, Abu Zeeshan; Al-Shenqiti, Abdullah; Khan, Saad Jawaid (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate the amputees’ satisfaction with their prostheses and with the clinical services. Method: The cross-sectional study was conducted at the Medical Rehabilitation Hospital, Madinah, Saudi Arabia, from August 2018 to November 2019, and comprised unilateral, traumatic lower limb amputees. Data was collected using the client satisfaction with the device, and the client satisfaction with service modules of the Orthotics and Prosthetics User's Survey instrument. Data was analysed using SPSS 23. Result: Of the 220 subjects, 43(19.54%) were transfemoral amputees; 37(86%) males with a mean age of 51.9±12.7 years, and 6(14%) females with mean age 51.9±12.7 years. There were 168(76.36%) transtibial amputees; 146(87%) males with mean age 51.7±12.9 years, and 22(13%) females with mean age 54.1±12.7 years. Besides, there were 9(4.09%) female partial-foot amputees with a mean age of 36.0± 6.5 years. Overall, 165(75%) subjects were satisfied with the durability of their prostheses, and 213(97%) were satisfied with the service standard. Conclusion: Most of the participants were generally satisfied with their prostheses, and almost all of them were generally satisfied with the clinical services. Key Words: Amputees, Artificial limb, Lower extremity, Patient satisfaction, Rehabilitation centres, Surveys, Questionnaire.